KONDISI FISIK DAN SARANA SANITASI DASAR RUMAH DI PERMUKIMAN KELURAHAN TANAH KALIKEDINDING KOTA SURABAYA TAHUN 2021 - Muhammad Gilang Ramadhan; Narwati; Fitri Rokhmalia (Jurnal Hygiene Sanitasi, 2021)
The problems of physical condition and basic sanitation facilities in Tanah Kalikedinding Urban Village are the condition of dull and cracked walls, lack of lighting, ventilation that does not meet the requirements and the application of healthy latrines as a means of disposing of public feces has not been optimal. The purpose of this study was to assess the physical condition and basic sanitation facilities of houses in the Tanah Kalikedinding urban village of Surabaya. This study used a descriptive type of research with a cross sectional approach. The population in this study were 351 houses in Tanah Kalikedinding Village. Sampling using simple random sampling technique with a total sample of 57 houses. Analysis of data regarding the physical condition and basic sanitation of the house is based on the results of observations and then compared with Kepmenkes No. 829/Menkes/SK/VII/1999 concerning housing health requirements, components and spatial arrangement of healthy homes. The results showed that the physical condition of the house in Tanah Kalikedinding Village got a good category (83.76%). However, the components of the floor assessment, which are clean and watertight, and the components on the walls, namely light colored walls, do not meet the requirements. Meanwhile, basic sanitation facilities also received a good category (92.37%). However, in the assessment component of waste disposal facilities, namely water flowing smoothly and using closed channels, it does not meet the requirements. The conclusion of this study was that the assessment of the physical condition of the house and basic sanitation facilities in Tanah Kalikedinding Village obtained the results of getting a good category. The researcher hopes that the results of this research will be useful for the application of science to the community in the field of environmental health.